2006
DOI: 10.1111/j.1460-9568.2006.04642.x
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal vulnerability following traumatic brain injury: a potential role for neurotrophin‐4/5 in pyramidal cell neuroprotection

Abstract: Traumatic brain injury (TBI) causes selective hippocampal cell death, which is believed to be associated with cognitive impairment observed both in clinical and experimental settings. Although neurotrophin administration has been tested as a strategy to prevent cell death following TBI, the potential neuroprotective role of neurotrophin-4/5 (NT-4/5) in TBI remains unknown. We hypothesized that NT-4/5 would offer neuroprotection for selectively vulnerable hippocampal neurons following TBI. Measurements of NT-4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 113 publications
4
57
0
1
Order By: Relevance
“…The Viano et al (2005b) study demonstrated that the typical deformation of the hippocampus to be 4-6 mm in concussion associated with professional football. Numerous human and animal studies have demonstrated the vulnerability of the hippocampus (and fornix) to injury in TBI Geddes et al, 2003;Royo et al, 2006;Tashlykov et al, 2007;Tasker et al, 2005;Wilde et al, 2006b) and functional neuroimaging studies using SPECT also demonstrate medial temporal lobe hypoperfusion in mTBI (Gowda et al, 2006). Thus, given the location of the hippocampus in the medial temporal lobe and its connection and location to the fornix, these brain regions are key to understanding PPCS neuropsychology, and should be the focus of intense neuropsychological investigation.…”
Section: Vulnerability Of the Medial Temporal Lobe And In Particularmentioning
confidence: 99%
“…The Viano et al (2005b) study demonstrated that the typical deformation of the hippocampus to be 4-6 mm in concussion associated with professional football. Numerous human and animal studies have demonstrated the vulnerability of the hippocampus (and fornix) to injury in TBI Geddes et al, 2003;Royo et al, 2006;Tashlykov et al, 2007;Tasker et al, 2005;Wilde et al, 2006b) and functional neuroimaging studies using SPECT also demonstrate medial temporal lobe hypoperfusion in mTBI (Gowda et al, 2006). Thus, given the location of the hippocampus in the medial temporal lobe and its connection and location to the fornix, these brain regions are key to understanding PPCS neuropsychology, and should be the focus of intense neuropsychological investigation.…”
Section: Vulnerability Of the Medial Temporal Lobe And In Particularmentioning
confidence: 99%
“…These knockout mouse studies provide support for the usefulness of NT-4/5 therapy after trauma. Indeed, supplementation of NT-4/5 levels through post-traumatic intracerebral infusion of recombinant protein reduced hippocampal CA2/3 pyramidal neuronal loss following lateral fluid percussion brain injury in rats [99].…”
Section: Neurotrophins (Nt-4/5 Bdnf)mentioning
confidence: 96%
“…Brain injury elicits an increase in expression of multiple growth factors including neurotrophins, which is often transient and limited to traumatic penumbra [99][100][101]. Supplementing this response by exogenous growth factor administration promotes functional improvement and neuroprotection following experimental TBI [99,101,102].…”
Section: Neurotrophins (Nt-4/5 Bdnf)mentioning
confidence: 99%
See 2 more Smart Citations